Matlab/Simulink Modeling of Parallel Resonant DC Link Soft-Switching Four-leg SVPWM Inverter - Omar, Riyadh G.; Thejel, Rabee' H. (Iraqi Journal for Electrical and Electronic Engineering, 2015)
This paper suggests the use of the traditional parallel resonant dc link (PRDCL) circuit to give soft switching to the Four-leg Space Vector Pulse Width Modulation (SVPWM) inverter. The proposed circuit provides a short period of zero voltage across the inverter during the zero-vectors occurrence. The transition between the zero and active vectors accomplished with zero- voltage condition (ZVC), this reduces the switching losses. Moreover, the inverter output voltage Total Harmonic Distortion (THD) not affected by circuit operation, since the zero voltage periods occur simultaneously with zero-vector periods. To confirm the results, balanced and unbalanced loads are used. Matlab/Simulink model implemented for simulation.